2017
DOI: 10.2169/internalmedicine.56.8039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Rheumatoid Arthritis Patients Achieving Functional Remission with Six Months of Biological DMARDs Treatment

Abstract: Objective Although previous studies have reported the prognostic factors for functional remission, no reports have cited the predictive factors. Our aim was to study the predictive factors for functional remission, which is a treatment goal in rheumatoid arthritis (RA), after receiving biological disease-modifying antirheumatic drugs (bDMARDs) treatment for six months. Methods The study consisted of 333 RA patients treated with bDMARDs for six months. The following patient characteristics were investigated: ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Multiple previous studies have reported clinical and imaging remission in patients with RA, but few studies have focused on functional remission [4,30]. In the present study, we investigated important factors associated with QOL in patients with RA, and our findings suggest that the disease duration, PDQ, PSEQ, PCS, use of oral steroids, and use of oral analgesics play important roles in achieving functional remission.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Multiple previous studies have reported clinical and imaging remission in patients with RA, but few studies have focused on functional remission [4,30]. In the present study, we investigated important factors associated with QOL in patients with RA, and our findings suggest that the disease duration, PDQ, PSEQ, PCS, use of oral steroids, and use of oral analgesics play important roles in achieving functional remission.…”
Section: Discussionmentioning
confidence: 73%
“…RA affects approximately 0.5–1% of the population globally [ 3 ]. The combination of methotrexate and biological disease-modifying antirheumatic drugs (bDMARDs) has contributed to an increase in the number of patients who achieve clinical remission [ 4 ]. Disease activity in RA is often assessed using the disease activity score in 28 joints (DAS28) [ 5 ], which can further be combined with the C-reactive protein level (DAS28-CRP).…”
Section: Introductionmentioning
confidence: 99%
“…In a German longitudinal database, depression was present in 22% of the 1072 elderly RA patients (mean age 72 years), and dementia, cancer, osteoporosis, hypertension and diabetes were associated with a higher risk of developing depression [149]. Moreover, depression is associated with increased global mortality in RA [150], suicide death in RA and PsA [151], and reduced likelihood of joint remission in RA and PsA [152, 153]. However, anti-depressants are frequently associated with side effects and have inconstant benefits in pain management or functional status [154].…”
Section: Ways To Improve Care Of the Elderlymentioning
confidence: 99%
“…В немецкой базе данных депрессия присутствовала у 22% из 1072 пожилых пациентов с РА (средний возраст 72 года), при этом риск развития депрессии был выше при наличии деменции, рака, остеопороза, гипертонии и диабета [151]. Более того, депрессия связана с повышением общей смертности при РА [152], смерти от суицида при РА и ПсА [153], а также снижением вероятности достижения ремиссии при РА и ПсА [154,155]. Однако при назначении антидепрессантов часто развиваются побочные эффекты, а их эффективность при коррекции болевого синдрома и функциональных нарушений не всегда предсказуема [156].…”
Section: гериатрический подходunclassified